PERAN SERTA KELOMPOK SADAR WISATA (POKDARWIS) DALAM PENGEMBANGAN DESA WISATA DI DESA TARO KECAMATAN TEGALLALANG KABUPATEN GIANYAR - Ni Wayan Sutiani (Jurnal Ilmiah Cakrawarti, 2021)
Taro Tourism Village which has natural potential as a supporting asset in tourism development is an activity to manage and develop a tourist attraction. The development of tourism in Taro village was carried out by the Tourism Awareness Group of the Taro Tourism Village which was formed by the Ministry of Tourism and Creative Economy and gave birth to this Tourism Awareness Group. This Pokdarwis is a community-based volunteer organization with the hope of realizing Sapta Pesona in increasing tourism development in the village.The problem raised in this study is how the role of the Tourism Awareness Group (Pokdarwis) in Taro Village in the development of tourism in the Taro Tourism Village. This study uses a qualitative descriptive method by emphasizing the aspect of in-depth understanding of the Taro Tourism Village in the development of a tourist village even though it is still facing a pandemic situation but is more focused on maintaining its natural assets.